Challenges and Opportunities in India’s Agricultural Marketing: A Comprehensive Qualitative Study - Jashwant, Sandeep (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
India's agricultural sector, a cornerstone of its economy, faces multifaceted challenges and opportunities in its marketing landscape. This comprehensive qualitative study delves into the intricate dynamics of agricultural marketing in India, examining the obstacles and prospects that shape the sector's performance. Through in-depth interviews, focus group discussions, and secondary data analysis, this study explores the key challenges, such as infrastructure deficits, regulatory constraints, market inefficiencies, and the impact of climate change, while also identifying emerging opportunities like digital marketing, value addition, sustainable agriculture practices, and policy reforms. The findings provide actionable insights for policymakers, farmers, and stakeholders to enhance the effectiveness and sustainability of agricultural marketing in India.